2018
DOI: 10.1111/anae.14244
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the tolerability of the Cook staged extubation wire in patients with known or suspected difficult airways extubated in intensive care

Abstract: The Cook staged extubation set (Cook Medical) has been developed to facilitate management of the difficult airway. A guidewire inserted before tracheal extubation provides access to the subglottic airway should re-intubation be required. This prospective cohort study examines patients' tolerance of the guidewire and its impact on clinical status around tracheal extubation in the intensive care unit. Vital signs, incidence of symptoms and patient tolerance of the wire were recorded. Twenty-three patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A small preliminary study suggested high tolerance, as 17 of 23 patients (73%) tolerated the wire for 4 hours, although "tolerated" was not further quantified. 19 Success rate and dislocation rate have not been proven to be different from the conventional AEC: Nasal endoscopy was performed in 11 of these patients and revealed one wire dislocated to the esophagus, which would correspond to a dislocation rate of 9%. In another recent small study, Furyk et al…”
Section: Discussionmentioning
confidence: 90%
“…A small preliminary study suggested high tolerance, as 17 of 23 patients (73%) tolerated the wire for 4 hours, although "tolerated" was not further quantified. 19 Success rate and dislocation rate have not been proven to be different from the conventional AEC: Nasal endoscopy was performed in 11 of these patients and revealed one wire dislocated to the esophagus, which would correspond to a dislocation rate of 9%. In another recent small study, Furyk et al…”
Section: Discussionmentioning
confidence: 90%
“…To further improve the tolerance to the AEC, a wire-based AEC is available (Cook Staged Extubation Catheter™, Cook Medical Inc., Bloomington, IN, USA). A small preliminary study suggested high tolerance, as 17 of 23 patients (73%) tolerated the wire for 4 h, although “tolerated” was not further quantified [19]. Success rate and dislocation rate have not been proven to be different from the conventional AEC: Nasal endoscopy was performed in 11 of these patients and revealed one wire dislocated to the esophagus, which would correspond to a dislocation rate of 9%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability of the CSES in critically ill patients remains unclear from their work. The authors reported accidental removal of the guidewire in 4 out of 23 cases, one on extubation, one due to cough and two due to patient agitation . A previous study reported a failed intubation rate of 2 out of 23 when the CSES was used to intubate anatomically favourable airways that were adjusted to a Cormack and Lehane Grade 3 or 4 in order to simulate difficulty.…”
mentioning
confidence: 95%
“…The focus of McManus et al. 's study was to assess the tolerability of this device in the critically ill population and the authors have provided a useful addition to the literature in this regard .…”
mentioning
confidence: 99%